Bioaugmentation Effect of Bacillus sp. and Pseudomonas sp. Isolates on Lowering Used Lubricating Oil- Contaminated Soil pH - Mutia Dwi Herakasih; Yuni Ahda (Universitas Negeri Padang, 2019)
The purpose of this study was to look at the effect of bioengineering on the pH value of used oil contaminated soil. This research was conducted from February to April 2018. This study used Pseudomonas sp. Isolates. and Bacillus sp. from previous research by Ahda and Fitri (2016). The bacterial formulations are Pseudomonas sp, Bacillus sp, and consortium. The number of biaoaugmentation used in this study was 6 times the fermentation. Calculation of pH values is done once a week and carried out for 42 days of the study period. The results of this study indicate that bioaugmentation affects the pH value of used oil contaminated soil.